Construção e validação de cenários de simulação de Suporte Básico de Vida na Atenção Básica - Carreiro, Bruno Oliveira (2020)
This study aimed to develop and to validate six medium fidelity Basic Life Support clinical simulation scenarios in Primary Health Care. Development and content validation descriptive study. American Heart Association Guidelines for Cardiopulmonary Resuscitation and Emergency Cardiovascular Care and Cardiovascular Prevention Guideline of the Brazilian Society of Cardiology between 2015 and 2019 were used to develop the scenarios. According to Fabri et al. (2017), author elaborated seven criteria for scenarios: previous student knowledge, learning objectives, theoretical foundation of activity, scenario preparation, scenario development, debriefing and evaluation. A list of experts was prepared based on network professor adviser. Experts received two attachments: a document containing the scenario, the sociodemographic characterization and the scale of agreement and Free and Informed Consent Form (ICF). Experts who did not respond the validation through emails we sought and those who partially responded were excluded. The sample was consisted for seven experts. Medical or nurses experts with experience in clinical simulation and BLS and minimum master's degree validated and judged those scenarios according to Content Validation Index (IVC). Majority of them were between 35 and 45 years old, were nurses, had doctorate as maximum degree, worked as teacher, had professional experience up to 14 years and experience in clinical simulation time of 5 to 8 years, had Basic Life Support experience of 13 years or more. Scenarios obtained CVI between 85.7% and 100%, and experts' suggestions were incorporated into the scenarios. Construction and validation of clinical simulation scenarios brings greater reliability to scenarios thems and make facilitators waste less time for their construction, however there is not adaptation to local peculiarities. In addition, it allows its reapplication by other professionals, facilitators, teachers or scholars who work with clinical simulation.